The Influence of Training and Human Resource Development on The Performance of Employees of The Morning Afternoon Restaurant, Basuki Rahmat Branch, Palembang City - Ersa Dinda; Hamid Halin; Muhammad Bahrul Ulum (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine how the Effect of Human Resources Training and Development on Employee Performance of the Palembang City Branch of the Pagi Sore Restaurant. The method used in this study uses a quantitative approach. The data collection technique used the distribution of questionnaires with a sample size of 60 respondents. The data analysis tools used are classical assumption test, multiple linear regression analysis, t test, F test, and coefficient of determination. Data processing using SPSS version 24 for windows. Based on the results of the study, it shows that the Training variable with a significant value (0.000) which means that training partially has a positive and significant effect on employee performance, the Human Resource Development variable with a significant value (0.039) which means that Human Resource Development partially has a positive and significant effect on employee performance. Training and HR Development simultaneously have a positive and significant effect on employee performance with a significant value (0.000).